Diagnosis of Compliance of Micro and Small Businesses in Halal-Certified Product Assurance - Aqiqi, Siti Lutfi Nur; Alim, Mohammad Nizarul (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2025)
This study aims to analyze the challenges and compliance of business actors in implementing halal certification, especially among SMEs in Surabaya. Using a qualitative approach, this study conducted in-depth interviews with steak business owners, halal supervisors, and halal auditors, and was supported by direct observation and documentation analysis. The results of the study revealed some of the main challenges faced by SMEs in the halal certification process, including administrative complexity in managing NIB and documentation, limited access to halal-certified raw material suppliers, and lack of effectiveness of mentoring from halal supervisors. The post-certification monitoring system is also not optimal, as seen from the practice of borrowing names and the absence of periodic reporting obligations. This study recommends the need to strengthen the continuous monitoring system, increase socialization and evenly distributed training, integrate halal policies with company SOPs, and adequate financial suppor